Infertility, Assisted Reproductive Technologies and Hormone Assays - Sultan Sheriff, Dhastagir (IntechOpen, 2019)
Infertility is a major public health concern and medical condition that afflicts millions globally. As such, many people seek reproductive care with the goal of receiving a proper diagnosis and a successful outcome using assisted reproductive technology (ART). Infertility: Assisted Methods of Reproduction and Hormonal Assays provides an overview of ART methods and discusses recent trends in the field. Chapters cover an array of topics including diagnosis of infertility using hormonal assays, adverse outcomes of ART, oocyte donation, cryopreservation of oocytes and embryos and psychosocial care.